Smart interventions in floriculture for enhanced shelf-life and value-addition - Sindhu, S S; Gupta, Sachi (Indian Horticulture, 2024)
The use of advanced post-harvest treatments, and sustainable packaging solutions has revolutionized flower preservation and value-addition. These smart interventions focus on reducing spoilage, maintaining aesthetic quality, and optimizing resource use. Additionally, value-addition techniques such as the development of bio- preservatives, decorative enhancements, and eco-friendly packaging solutions further contribute to increasing market appeal and sustainability. The integration of these technologies not only improves the profitability of the floriculture sector but also aligns with global trends in sustainability and consumer preferences for eco-friendly products. This article highlights the crucial role of innovation in driving the future of floriculture towards a more efficient, profitable, and sustainable direction.